(3TaGA GdYdjd Ydi GdefL GdefJNHs - (3Ydj Hf bGSe Hf eMeO GdJLjHj, CHh GdMSf, GdeYQha HGdRbGbs; (3Ydj Hf MGJe Hf eMeO GdJLjHj GdeZQHj, CHh GdMSf,J (B912 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje CeG HYO agPG JbjjO jchf cGdTQM eRLJg HfXe GdEeGe CHj GdMSf Ydi Hf GdbGSe GdRbGb GdeSei GdefgL GdefJNH Edi bhGYO GdePgH bUOJ ajg Md eG jMJGL Edi GdMd ef CdaGXg heG jJhba Ydjg ageg HHjGf EYQGHg s
(3BNQgG (B:s
(3hai QhGjI dGJfbV GdSGYI MJi jVQH GdaCS ef cd fGMjI Edi YGde GdeOjfI jWdHhf Ydeg hbO Jdhf GdCFeI Ydi eGdc MJi EPG bjd gPG bhd YGde GdeOjfI jYfi SajGf Hbhdg cGfhG GdJGHYjf GfJgi hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI efbhdg Yf fSNI HNW GdeDda hebGHdI YdjgG hYdjgG HYV GdJUMjMGJ s
(3heYfhfI HGdMHQ GdCMeQ s
(3hYdi GdUaMI GdChdi eSCdI abgjI ai GdUabI s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs